2008
DOI: 10.1016/j.amepre.2008.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Use of a Health Plan–Sponsored Physical Activity Program by Older Adults

Abstract: Background-The purpose of this study was to determine the associations between depression and the likelihood of enrollment in a health plan-sponsored physical activity program and pattern of program participation over 2 years; a secondary aim was to examine the association between participation dose and depression risk. There are no published studies on how depression influences participation in health plan-sponsored physical activity programs and how participation affects depression risk in older adults in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 49 publications
1
22
0
1
Order By: Relevance
“…Results showed that nondepressed participants who attended fitness classes at least 2 times per week in the first year of the program were 46% less likely than control subjects to become depressed in the following year (P ¼ 0.002); a similar effect was observed among previously depressed participants but this did not achieve statistical significance (P ¼ 0.06). 39 Further, because physical activity has been shown to mimic the effects of antidepressants, 40 these findings suggest the possibility that programs may enable a reduction in prescriptions, and the associated costs, for these types of medications.…”
Section: Review Of Senior Wellness Outcomes S-47mentioning
confidence: 96%
“…Results showed that nondepressed participants who attended fitness classes at least 2 times per week in the first year of the program were 46% less likely than control subjects to become depressed in the following year (P ¼ 0.002); a similar effect was observed among previously depressed participants but this did not achieve statistical significance (P ¼ 0.06). 39 Further, because physical activity has been shown to mimic the effects of antidepressants, 40 these findings suggest the possibility that programs may enable a reduction in prescriptions, and the associated costs, for these types of medications.…”
Section: Review Of Senior Wellness Outcomes S-47mentioning
confidence: 96%
“…This study's findings with regard to emotional health are associative and add research support to a prior study of the positive impact of SilverSneakers participation associated with a lower risk of depression. 18 Research by Ozminkowski et al indicates that, when combined with other chronic conditions, depressive symptoms result in an even greater negative impact on quality of life. 34 The demonstrated benefits of SilverSneakers participation to both emotional and physical health measures denote the strong positive impact the program can have on the well-being of seniors.…”
Section: Discussionmentioning
confidence: 99%
“…These results are thus complementary to Nguyen and Ackermann's research displaying slower growth in health care costs among seniors who participated in a health plan-sponsored fitness program. [17][18][19][20][21] Social engagement is beneficial to the health and wellbeing of America's seniors. Recent research by Thomas shows that increasing social engagement was associated with a lower risk of mortality, after accounting for other known predictors of mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to develop interventions to improve physical activity, and thus physical and mental well-being in depressed people aged 60 and over, more knowledge is needed about the current level and the determinants of physical activity in late-life depression (Nguyen et al, 2008). Characteristics that have been demonstrated to be associated with physical activity as well with depression can be clustered into cognitive function (Hoffman et al, 2008), somatic condition (Antonelli Incalzi et al, 2005), other lifestyle factors (Duivis et al, 2011) and psychosocial and environmental factors (Harvey et al, 2010;Trost et al, 2002).…”
Section: Introductionmentioning
confidence: 99%